Motivation -- Goal orientation among middle school students - Byrne, Sara (My University, 2010)
The present study examined achievement goal orientations among middle school students to examine potential differences in goal orientations between students' developmental level and/or gender. The relationship between students' personal achievement goals and their perception of the classroom goal orientations was also investigated. Three hundred and sixty eight students were sampled across seventh and ninth grade from a junior high located in a Midwest town using a 28-item survey. A MANOVA revealed that boys are more likely to hold performance-approach goals than girls, and perceived their classroom to be more performance-approach or performance-avoidance oriented than girls. Results also found a small positive relationship between students' personal achievement goals and their perceptions of the classroom goal orientations. Finally, the subject type students were given (English, math, social studies, science) was found to impact students' perception of classroom orientations. Math and social studies were perceived as being more mastery oriented than English and science. No other significant effects or interactions found. The obtained results from the study show support for gender differences in students' achievement goals, and the slight influence the classroom can have on students' personal achievement goal orientations.
Keywords: Achievement motivation in children; Middle school students -- Psychology; Goal (Psychology)